Struktur Komunitas Makrozoobentos Di Perairan Rawa Banjiran Sungai Rungan, Kota Palangka Raya - Infa Minggawati (Fakultas Peternakan Universitas Kristen Palangka Raya, 2013)
This study was conducted to determine the structure of macrozoobenthos community in Rungan river floodplain ecosystem and compare macrozoobenthos abundance in each sampling station. This study was conducted in October 2013 located in one of the existing swamps of Rungan river floodplain is in Dapur Lake, Marang District, Palangka Raya. With the number of observation stations as much as 4 station is at the inlet , middle and outlet of the swamp . The method used is the method of survey, and samples then analyzed in the laboratory . The result is a diversity of macrozoobenthos in station 1, there are 4 classes of insect, station 2 there are 5 classes of insects and nematodes, station 3 there are 3 classes of insects and at station 4 there is one class of insect. The macrozoobenthos dominance is Zavrelimyia sp at station 1 , Procladius sp at station 2, whereas for station 3 is dominated by Chironomus sp and Clinotanypys sp, at station 4 is dominated by Chironomus sp . The highest density of macrozoobenthos 755 ind/m2 at stations II and the lowest density 89 ind/m2 at station IV. The higest diversity index (H ') at station II and the lowest at station IV . Index of Evenness (E) was highest at stations III and the lowest at station IV , with the dominance index was highest at station IV (by Chironomus sp).